Synthesis of zinc-cobalt bimetallic oxide anchored on the surface of rice husk carbon as anode for high-performance lithium ion battery. (December 2019) - Yu, Kaifeng; Wang, Le; Wang, Xiaofeng; Liu, Weiping; Liang, Jicai; Liang, Ce
Abstract: As an anode of lithium ion battery, bimetallic oxides have received considerable attention owing to the high theoretical specific capacity, while their inherent poor conductivity and large volume changes during cycling have limited rate performance and cycle stability and blocked further application. In this work, a novel compound zinc-cobalt bimetallic oxides anchored on the surface of 3D amorphous rice husk-derived carbon matrix has been prepared through a facile method. When used as anode for lithium ion battery, it displays a high charge capacity of 972 mAh g −1 over 150 cycles at 100 mA g −1 . The excellent electrochemistry performance is attributed to the introduction of rice husk-derived carbon, which improves the electronic conductivity of ZnO/CoO nanoparticles and solves the rapid decay of lithium-ion battery capacity caused by volume expansion. This work not only supplies an advanced electrode for energy storage devices, but also provides an effectively way to utilize agricultural residues. Highlights: Rice husk is used as carbon source to prepared 3D amorphous carbon matrix. Zinc-cobalt bimetallic oxides are anchored on the surface of carbon matrix through a facile method. When used as anode for lithium ion battery, this nanocomposite has displayed an excellent electrochemistry performance.